Diabetes mellitus tipo 2 como factor de riesgo de infección tras artoplastía total de cadera - Pretell Vargas, Crystel Yasmín (2017)
Demostrate if Diabetes Mellitus is an associated factor to hip prosthes infection at Victor Lazarte Echegaray Hospital. MATERIAL AND METHOD: Was conduced an analitic, observational, retrospective, control and cases investigation. The study population was conformed for 108 postoperated patients of hip arthroplasty at “Victor Lazarte Echegaray Hospital” of Trujillo between enero 2009 – diciembre 2014 by inclusion and exclusion criteries distributed in 2 groups: with and without prosthes infection. RESULTS: The prevalence of Diabetes Mellitus in hospsitalizated patients with and without hip prosthes infection were 56% and 35% respectively. Odss ratio to Diabetes Mellitus related to infection total hip prosthes were 2.38 (p<0.05). CONCLUSION: Diabetes Mellitus is a risk condition associated to infection total hip prosthes in hospitalizated patients